SURVEY KEBUGARAN JASMANI MELALUI TES KEBUGARAN PELAJAR NUSANTARA PADA SISWA KELAS VIII SMP NEGERI 1 KUOK - Azwan, Muhammad; Juita, Ardiah; Rahmatullah, Muhammad Imam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2025)
Abstract: The purpose of this study was to determine the physical fitness survey through the Indonesian student fitness test on class VIII students of SMP Negeri 1 Kuok. The average score of the Indonesian Student Fitness Test (TKPN) of 1.55 in grade VIII students of SMP Negeri 1 Kuok places them in the Poor category, which objectively reflects the inability of the majority of students to meet basic physical demands such as cardiovascular endurance, muscle strength, and agility. The range of values 1–1.9 in the TKPN norm indicates that 76.92% of students (19.23% Very Poor and 57.69% Poor) have a fitness capacity below the national average for their age group. This has implications for short-term health risks, such as fatigue during distance learning or extracurricular activities, as well as decreased quality of life due to limitations in optimal participation in the social environment. Furthermore, the Sit Up scores (18.38) and Pacer Test (18.92) which are in the Very Low category indicate weak core muscle endurance and cardiorespiratory system, which are important foundations for physical growth and cognitive development of adolescents. Without intervention, this condition has the potential to worsen learning motivation and increase the risk of degenerative diseases in adulthood.Keywords: Physical fitness survey, student fitness test